Association Between Maintenance Immunosuppressive Regimens and COVID-19 Mortality in Kidney Transplant Recipients. Issue 10 (27th July 2022) - Gérard, Alexandre O.; Barbosa, Susana; Anglicheau, Dany; Couzi, Lionel; Hazzan, Marc; Thaunat, Olivier; Blancho, Gilles; Caillard, Sophie; Sicard, Antoine; ,
Abstract : Background: Solid organ transplant recipients are at high risk for fatal forms of coronavirus disease 2019 (COVID-19). We conducted a cohort study among kidney transplant (KT) recipients from the French Solid Organ Transplant COVID-19 Registry to investigate the association between maintenance immunosuppressive drugs and 60-d mortality. Methods: Data from all KT recipients with COVID-19 included in the French Solid Organ Transplant COVID-19 Registry between February 28, 2020, and December 30, 2020, were retrieved. We evaluated associations between immunosuppressive drugs and death within 60 d using logistic regression, with all baseline characteristics considered to influence outcome or immunosuppressive regimen. The Benjamini-Hochberg correction was used for controlling false positive rate; 40 multiple imputations were performed. Adjusted P value <0.05 was considered statistically significant. Results: There were 1451 KT recipients included. Median age was 58 y, and 66.4% were men. Most frequent comorbidities were hypertension (81.9%), diabetes (34.5%), and cardiovascular disease (29.5%). Median time since transplant was 71 mo. Maintenance immunosuppression regimens included calcineurin inhibitors (1295, 89.2%), antimetabolites (1205, 83%), corticosteroids (1094, 75.4%), mammalian target of rapamycin inhibitors (144, 9.9%), and belatacept (58, 4.0%). Among 1451 transplant recipients, 201 (13.9%) died within 60 d. Older age and higher baseline serum creatinine were associated with mortality (odds ratios, 1.09 [1.07-1.11] and 1.01 [1.005-1.009], P < 0.001). Corticosteroid-free regimens were associated with a significantly lower risk of death (odds ratio, 0.48 [0.31-0.76]; P = 0.011). Conclusions: Corticosteroid-free regimens were associated with a lower risk of death in KT recipients with COVID-19. Long-term exposure to corticosteroids impairs immune functions and may predispose solid organ transplant recipients to severe forms of COVID-19. Abstract :